Peer counseling training and self-motivation at Universitas Muhammadiyah Yogyakarta - Rizqi, Muhammad Arif; Najiha, Fathia (Institute of Computer Science (IOCS), 2025)
Adolescents were vulnerable to mental health challenges as they faced new environments and experiences. To support them, the Student and Alumni Development Institute at Universitas Muhammadiyah Yogyakarta provided counseling services through peer counselors. However, these peer counselors experienced low motivation and limited confidence due to the absence of structured training. This study aimed to examine the effect of peer counseling training on the self-motivation of peer counselors. A quantitative study with a quasi-experimental one-group pretest–posttest design was conducted involving 31 peer counselors selected through total sampling. The intervention consisted of structured peer counseling training sessions. Data were analyzed using the Wilcoxon test. Results showed a significant increase in self-motivation scores after training compared to before (p = 0.043). These findings indicated that peer counseling training effectively improved the self-motivation of peer counselors. Strengthening training programs may enhance the quality of counseling services provided to adolescents through peer-based interventions.